Cruel and Unusual What? Toward a Unified Definition of Punishment - Donelson, Raff (2016)
This Article argues for an expanded understanding of legal punishment for American courts to use. Punishment, on this new view, includes all significant harm caused by state actors’ retributive intent and most significant harm that befalls someone as a result of the state seeking retribution against her. What commends this new definition is not that it tracks lexicographers’ or metaphysicians’ understandings of punishment; rather, this new definition aims to track relevant moral and political considerations. Importantly, the proposed definition results from an attempt to reason from the perspective of someone harmed by state practices, as that perspective has greater moral import than perspectives of courts, lawmakers, or corrections officials